RANCANG BANGUN SISTEM INFORMASI PENCATATAN DAN PELAPORAN TERPADU PUSKESMAS - Sri Herawati; Moh. Adi Purnomo (Universitas Muhammadiyah Ponorogo, 2016)
Community Health Center is a public facility that aims to organize the efforts of public health and the individual health first rate. SP2TP (Recording and Reporting System Integrated Health Center) is an evaluation of program success and improvement of health center services in an effort to improve the health of communities as high. PHC and SP2TP are two very important things in the world of health. SP2TP report on the health center has a very important role so that the process of recording and reporting formats and procedures need to be equalized. SP2TP in research can resolve these problems. This information system is an integrated system of all health centers and health offices. The results of this research are the process of recording and reporting SP2TP is easier to use and able to produce accurate, complete, and on time SP2TP reports.